The Jewish revolt against Rome : interdisciplinary perspectives - Popovic, Mladen. (Supplements to the Journal for the Study of Judaism, 2011)
The Jewish revolt against Rome in the first century C.E. provides ancient historians the opportunity to study one of the best-documented provincial revolts in the early Roman Empire. This volume brings together different disciplines, some for the first time. The contributors draw from a wide range of literary, archaeological, documentary, epigraphic and numismatic sources. The focus is on historiographical and methodological reflections on our sources, their nature and the sort of historical questions they allow us to answer. This volume combines fields of research that should not be pursued in isolation from each other if we wish to further our understanding of the Jewish revolt's historical context.